PANCASILA DALAM KONTEKS PENDIDIKAN NILAI - Toni Nasution (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
The educational world has signs which became a reference for a goal that must be achieved nationally, that in a sense is very important and interesting for the mind that 1945 Preamble explicitly mentions about